A Case Report on Radiologic Findings of Thyrolipomatosis: a Rare Fat Containing Lesion diffusely Infiltrating throughout the Thyroid Gland - Kumar, Ravinder; Bhargava, Abhishek; Jaiswa, Gagan (Journal of Kathmandu Medical College, 2017)
A 73-year-old male presented with rapidly enlarging midline neck swelling of two months duration. Respiratory discomfort during breathing and hoarseness of voice occurred since few days. Clinical diagnosis was multinodular goitre. Sonography showed diffusely enlarged thyroid gland with altered echotexture. Multiple nodular echogenic lesions were noted in both the lobes. Unenhanced Computed tomography of the thorax and neck revealed a mass with no distinct margins and predominantly fat attenuation in both lobes of the thyroid gland. Magnetic Resonance images of the neck confirmed the fatty nature of the mass. These imaging findings signalled towards diffuse presence of mature adipose tissue inside thyroid gland which defi nes thyrolipomatosis. A near total thyroidectomy was performed and histopathological studies confirmed thyrolipomatosis in the post-operative specimen. Journal of Kathmandu Medical College Vol. 5, No. 2, Issue 16, Apr.-Jun., 2016